Effects of irrigation on coffee plants production and development of coffee in the west of Bahia state - Vicente, Marcelo Rossi; Mantovani, Everardo Chartuni; Fernandes, André Luis Teixeira; Neves, Júlio César Lima; Delazari, Fábio Teixeira; Figueredo, Edmilson Marques (Coffee Science - ISSN 1984-3909, 2017)
Irrigation redesigned the distribution of the cultivation of coffee in Brazil, and upon this, new studies in water consumption and in its relationships with production and growth in coffee became necessary. The objective of this work was to evaluate the effects of irrigation on the production and growth in coffee irrigated by drip irrigation, in the West region of Bahia. For this, a trial was carried out in the farm Café do Rio Branco, located in Barreiras – BA. The experiment was caried out with adult plants of coffee of the variety Catuaí Vermelho, approximately 3.5 years old and set up in a randomized block design, with five treatments and four replicates. The treatments corresponded to 75, 85, 100, 125 and 150% of the irrigation depth and were calculated by the Irriplus software. It was evaluated the productivity, water use efficiency (WUE), vegetative development, sieve classification, as well as the yield and maturation of fruits. A significant effect of the irrigation depth in yield, WUE and maturation of fruits (green and cherry) was observed at the end of four consecutive harvests. The estimated maximum productivity (60 sc ha-1), was obtained with 129% of the irrigation depth and a maximum WUE (5.7 kg mm-1) obtained with 75%. As to maturation, they were significant only for green (19.7%) and cherry fruits (67.5) with the irrigation depths of 119 and 121%, respectively. There was no significant effect of the different irrigation depths in the vegetative development, sieve classification and yield of fruits.